PENGARUH PENGETAHUAN GIZI PERILAKU MAKAN DAN AKTIVITAS FISIK TERHADAP STATUS GIZI REMAJA PUTRI DI SMA BABUSSALAM KOTA TANGERANG TAHUN 2020 - Septi Wulandari; Bambang Mardisentosa (Nusantara Hasana Berdikari, 2021)
The world's prevalence shows the nutritional status of teenagers aged 5-19 years, i.e. skinny 10.5%, fat 18.4% and obesity 6.8%. The one that is causing the problem of adolescent nutritional status in Indonesia is a lack of knowledge about nutrition, eating behaviors and physical activity. Research objectives to know the influence of nutritional knowledge of eating behaviors and physical activity on the nutritional status of young women in high school Babus Salam. In this study using causal comparative using a cross sectional approach. Sample techniques used Proposionate stratified random sampling as much as 74 respondents. Based on test T the nutritional knowledge is influential on nutritional status, The eating behavior has no effect to the nutritional status and physical activity to nutritional status. Based on the results of the F-test study of nutritional knowledge of eating behaviors and the physical activity of adolescents on nutritional status with results F table 7,510 with a value of sig 0.000.